SPECIFIC FEATURES IN BUILDING AND DEVELOPMENT OF RESIDENTIAL AREA IN SUBURBS OF LARGEST BELARUSIAN CITIES - Ya. S. Shcharbach; G. A. Potaev (Наука и техника)
The most challenging processes to be investigated further which are occurring in residential areas, suburbs in the largest Belarusian cities have been determined and systematized in the paper. The paper considers modern processes of transformation and development of residential areas on the studied territories; ongoing changes in the typology of dwellings and inhabitant composition of the suburban zones; problems pertaining to infrastructure development of suburban territories; preservation and improvement of recreational and ecological functions of the suburban zones in the largest cities. The paper presents a hypothesis on the possibility to modernize an urbanized region while using digital technologies and it also provides architectural and artistic characteristics of the residential environment. The main research methods are the following: field surveys; analysis of statistical data, project and regulatory documentation. So it has been revealed that it is necessary to carry out a detailed study of inhabitant composition in the settlements in order to determine their actual requirements in schools, kindergartens, and other facilities of public services. Development of town planning regulations taking into account actual typology of residential buildings and inhabitant composition is required for organization of suburban areas in the largest Belarusian cities. Current transformation processes of traditional settlement in the suburban zones of large cities are in need to have new requirements to their infrastructure development. It is necessary to improve a monitoring system and respond to population requirements and emerging problems. Nowadays there are conditions for formation of active population communities on the suburban territories. It is necessary to execute a coordinated development of all forms and types of suburban zones in the largest cities. The paper recommends to form, develop and preserve landscape and recreational areas in order to ensure an efficient recreational and ecological functions of the suburban zones.